Empowering Current and Future Educators: Using a Scalable Action Research Module as a Mechanism to Promote High-Quality Teaching and Learning in STEM - Esparza, David; Lynch-Arroyo, Ruby L.; Olimpo, Jeffrey T. (Frontiers in Education, 2022)
Professional development in action research methods can increase educators’ dispositions toward the adoption of evidence-based practices and data-based decision making. However, an in-depth review of the literature revealed that extant forms of action research professional development (ARPD) may not be accessible to all educators, as they are often relegated to full-semester undergraduate and/or graduate courses, internships, and teacher education programs. To address this issue, we designed, implemented, and assessed a scalable active-learning module on action research to strengthen the cognitive and affective outcomes of prospective and in-service STEM teachers (N = 26) enrolled in a cross-listed Scientific Teaching course, all of whom had not previously conducted action research. This three-session module integrated case studies, collaborative practice, group discussions, and instruction on action research theory and data collection methodologies. Analysis of pre-/post-intervention survey responses revealed that participants expressed greater self-efficacy related to their ability to design and conduct action research, strengthened knowledge of the process of action research, and greater awareness of the utility of data to inform research and teaching. When asked about the benefits of engaging in action research, participants suggested it could enhance their pedagogical content knowledge and reflectivity. However, participants identified logistical issues such as time constraints and resource availability, lack of institutional support, and possible student resistance to data collection as potential barriers to future action research practice. Overall, our module provides a scaffold to enculturate in-service educators to inquiry dispositions while offering a scalable approach to help prospective teachers in their transition to in-service practice.